FEMINISM INTERPRETATION: RECEPTION ANALYSIS OF PEKANBARU SOCIETY ABOUT ‘KARTINI’ MOVIE - Desliana Dwita; Desi Sommaliagustina (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
Film is one of medium of mass communication that brings message to be delivered to target audience. Film is not a value-free entity because it is the result of some people's thinking process until it becomes a cultural product. Hanung  Bramantyo's  Kartini  emphasizes  the  critical  attitude  of  a  woman  who  broke  the  injustice  in  the  era  of colonization  in  Indonesia.  She  can  be  regarded  as  the  early  struggle  of  feminist  figure  in  Indonesia  who  have brought  today’s  Indonesian  women  no  longer  experience  discrimination  in  education.  Nevertheless,  the interpretation of feminism has not been fully accepted because most of Indonesia territories adhere to patriarchal system.  The  specific  objective  of  this  research  is  to  find  out  the  reception  of  Pekanbaru  moviegoers  towards Kartini  in  regard  of  feminism  issue.  The  long-term  goal  of  this  research  is  to  provide  feedback  for  filmmakers about  Indonesian  audience  acceptance  towards  gender  equality  issues,  and  serve  as  a  reference  for  further research  on  gender  messages  in  the  media.  The  study  used  a  qualitative  research  method  with  the  reception analysis  approach  of  the  Stuart  Hall  Encoding  /  Decoding  model  which  observed  assimilation  process  between media discourse and audience culture discourse. Different understanding on emancipation and feminism causes different  interpretation.  Informants  who  have  a  strong  background  in  life,  interpret  feminism  as  a  struggle  to break injustice. Informants  who  were in the Dominant Hegemonic Position  group  were individuals  with a  high school  education  background  and  idolized  the  figure  of  Kartini.  Informants  who  are  in  Negotiated  Position  are individual  observers  and  film  practitioners.  Oppositional  Position  Informants  are  PhD  holder  individuals  and religious persons.  Keywords: Feminism, Reception Analysis, Kartini Movie